2009
DOI: 10.1021/es802632d
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the Pathogenic Prion Protein through Landfill Materials

Abstract: Transmissible spongiform encephalopathies (TSEs, prion diseases) are a class of fatal neurodegenerative diseases affecting a variety of mammalian species including humans. A misfolded form of the prion protein (PrP TSE ) is the major, if not sole, component of the infectious agent. Recent TSE outbreaks in domesticated and wild animal populations has created the need for safe and effective disposal of large quantities of potentially infected materials. Here, we report the results of a study to evaluate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 27 publications
4
38
2
2
Order By: Relevance
“…Various studies have demonstrated the binding and persistence of PrP Sc to soil and soil minerals. [93][94][95][96][97] Importantly, rodent-adapted scrapie remains infectious in bioassays when bound to soil minerals 93 and surprisingly, soilimmobilized prions have enhanced infectivity via the oral route compared to unbound prions. 94 Together, data suggest that soil is likely to be an important environmental reservoir of prion infectivity; however, it should be noted that to date no studies have demonstrated the presence of PrP Sc or prion infectivity in naturally contaminated soils.…”
Section: Environmental Sources Of Prionsmentioning
confidence: 99%
“…Various studies have demonstrated the binding and persistence of PrP Sc to soil and soil minerals. [93][94][95][96][97] Importantly, rodent-adapted scrapie remains infectious in bioassays when bound to soil minerals 93 and surprisingly, soilimmobilized prions have enhanced infectivity via the oral route compared to unbound prions. 94 Together, data suggest that soil is likely to be an important environmental reservoir of prion infectivity; however, it should be noted that to date no studies have demonstrated the presence of PrP Sc or prion infectivity in naturally contaminated soils.…”
Section: Environmental Sources Of Prionsmentioning
confidence: 99%
“…Laboratory studies designed to examine prion adsorption to and persistence in soils typically rely on extraction of PrP TSE from soil particles followed by immunodetection (e.g., immunoblotting, enzyme-linked immunosorbent assay) as the primary means of measurement (Cooke et al, 2007;Huang et al, 2007;Jacobson et al, 2009Jacobson et al, , 2010Johnson et al, 2006;Leita et al, 2006;Ma et al, 2007;Maddison et al, 2010;Russo et al, 2009;Seidel et al, 2007). To date, effective elution of PrP TSE from soil particles has been accomplished only with anionic detergents such as sodium dodecyl sulfate (SDS) or sodium N-lauroylsarconsinate (sarkosyl) (Cooke et al, 2007;Johnson et al, 2006;Seidel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that prions bind rapidly, and largely irreversibly to soils, do not migrate through soil columns and can persist for years. 20,22,23 Furthermore, the interaction of prions with soil does not remove infectivity. 24,25 This interaction of prions with soil is influenced not only by the soil type but also by the prion source.…”
Section: Resultsmentioning
confidence: 99%